Sri Lanka employment diagnostic study fostering workforce skills through education. (Metro Manila, Philippines Asian Development Bank, 2017)
Empowered Sri Lanka, Sri Lankas development policy document, envisions reorienting the country toward a modern and high value adding economy that is able to compete in the global market. Expanding the middle class and improving the living standards by creating one million jobs are at the core of the policy. This report seeks to support the realization of that vision by analyzing Sri Lankas employment situation and drawing recommendations from the analysis. The report starts with an overview of the labor market in relation to both supply and demand. It then looks at the issues of aging and skills generation. The concluding chapter examines links between labor market trends, informality, and poverty.
Keywords: Education -- Sri Lanka; Employment -- Sri Lanka; Electronic books